SIBLING RIVALRY ANTARA ANAK DENGAN MILD INTELLECTUAL DISABILITY DAN SAUDARA KANDUNG - Tejena, Nago; Valentina, Tience Debora (Jurnal Psikologi Udayana; Vol 2 No 2 (2015), 2015)
Human grow and develop throughout their life. There are several factors that influence human development. When there is an interference on these factors, it will cause developmental delays in children, such as intellectual disability. Children with intellectual disability require extra attention from the family. This will trigger a fight for resources between children with intellectual disability and their siblings. This situation will create conflict between them, which leads to sibling rivalry. The aim of this study is to determine the dynamics of sibling rivalry between child with mild intellectual disability and her siblings. This qualitative research is designed with case study approach. Sampling technique used is purposive sampling. Subject of this study is an 11 years old child with mild intellectual disability, who has two siblings. Data collecting techniques used are observation, interview, field note and audio- visual recording. The data were analyzed using data organization technique for qualitative study with case study approach according to Cresswell (1998). Based on the results from data organization,  this study found 33 categories that can be grouped into 6 patterns. The patterns are 1) sibling rivalry factors; 2) fight’s trigger; 3) types of sibling rivalry; 4) problem solving method when there is a conflict; 5) situation after the fight finished; and 6) the differences of point of view between subject and her siblings.   Keywords : sibling rivalry, mild intellectual disability, child.